2017
DOI: 10.1111/inr.12364
|View full text |Cite
|
Sign up to set email alerts
|

The structure of nursing: a national examination of titles and practice profiles

Abstract: Effective, patient-centred workforce planning must consider both the numerical and expertise mix of a nursing workforce. This research provides Australian health service and policy planners with evidence-base knowledge of the nursing workforce. Internationally, this research establishes a platform from which to develop validated tools and established processes to support replication of this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The recruitment and data collection strategy for the study have been reported in detail elsewhere (Gardner et al, ; Gardner et al, ). In summary, the recruitment process was by comprehensive dissemination of study information and invitation and instructions to participate via email, online and printed publication.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The recruitment and data collection strategy for the study have been reported in detail elsewhere (Gardner et al, ; Gardner et al, ). In summary, the recruitment process was by comprehensive dissemination of study information and invitation and instructions to participate via email, online and printed publication.…”
Section: Methodsmentioning
confidence: 99%
“…The subset of the national data set for analysis in this paper comprised front‐line managers, middle managers and RNs (as a comparator). These roles were identified with the results of the role delineation study described by (Gardner et al, ). A cluster analysis of the mean ARPD domain scores was performed to delineate nurses' roles then mapped against the position titles provided by respondents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a range of reasons behind this: the time for conducting research is often lacking (Bloomer & Cross 2011), whilst some CNC/CMCs perceive that it should not be a frequent part of their role (Wilkes, Luck & O'Baugh 2015), and others see it as an extra task (Cashin et al 2015). However, a more recently published study of Australian advanced practice nurses (including the CNC/CMC), found that these roles scored significantly higher at the advanced practice levels in the areas of research and professional leadership than did specialist and registered nurses (Gardner et al 2017). In this LHD, the CEO has provided ongoing support to nurses and midwives through the appointment of a Professor of Nursing and Midwifery Research.…”
Section: Edgar Et Almentioning
confidence: 99%